2012
DOI: 10.1055/s-0032-1315240
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Properties of Valeriana officinalis in the Zebrafish: A Possible Role for Metabotropic Glutamate Receptors

Abstract: Valerian extract is used in complementary and alternative medicine for its anxiolytic and sedative properties. Our previous research demonstrated valerian interactions with glutamate receptors. The purpose of this study was to determine if valerian anxiolytic properties are mediated by metabotropic glutamate receptors (mGluR) such as mGluR (1/5) (mGluR I) and mGluR (2/3) (mGluR II). Adult wild-type zebrafish (Danio rerio) prefer the black compartment and avoid the white compartment in the dark/light preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…For instance, valerian and valerenic acid have anxiolytic properties as tested with the dark/light preference task with zebrafish. This anxiolytic effect of valerian and valerenic acid is abolished after the administration of LAP3 (an mGluR I antagonist) and EGLU (an mGluR II antagonist) [39]. Furthermore, VE has a modest inhibitory effect on 3H dizocilpine (MK-801) binding, an indicator of NMDA-valerian interactions [40].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, valerian and valerenic acid have anxiolytic properties as tested with the dark/light preference task with zebrafish. This anxiolytic effect of valerian and valerenic acid is abolished after the administration of LAP3 (an mGluR I antagonist) and EGLU (an mGluR II antagonist) [39]. Furthermore, VE has a modest inhibitory effect on 3H dizocilpine (MK-801) binding, an indicator of NMDA-valerian interactions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Valerenic acid is considered to be the principal constituent [ 29 , 30 ]. The aqueous extract contain hydroxylvalerenic acid and acetoxyvalerenic acid in varying proportions [ 31 , 32 ]. The second objective of the work was to examine the anticonvulsant properties of valerenic acid alone, as well as the aqueous and ethanolic extracts of Valeriana officinalis.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the release of glutamate, we tested the hypothesis that the extracts in the study could act as agonists on mGluRs. In recent years, several studies have investigated the effects of VAL in the excitatory glutamate-mediated neurotransmission and showed that the extract of VAL and in particular valerenic acid are able to interact with Group I and Group II mGluRs, thus having calming and relaxing effects that may represent the main mechanism of action to explain the anxiolytic properties of this plant [21,22,47,48].…”
Section: Discussionmentioning
confidence: 99%